A new approach to the identification and selection of international technology transfer modes logical framework and empirical evidence - Venanzi, Daniela (Technovation)
The technical-legal form criterion for identifying international technology transfer modes is inadequate for the formulation of a mode strategy from the perspectives of the transacting firms. This paper develops a new approach which provides management with a conceptual and operational framework for selecting the appropriate means to transfer or acquire technology. The approach focuses on the identification of the key variables that differentiate the contractual modes of transfer. The analysis is supported by empirical evidence of real cases of technology transfer between small Italian firms and similar ones in newly industrialized countries.